Patient advocacy - Davis, Nichole (--For dummies., 2025)
Don't let the medical system push you around--empower yourself to take the lead. Feel more in control of your medical care and learn how to be your own advocate with Patient Advocacy For Dummies! Managing your own health care--or a loved one's--can be daunting, especially if you are diagnosed with a serious illness. This book helps you weigh all the treatments, make decisions, and speak up for yourself when you need to. You'll get advice on asking challenging questions in a way that will get the information you need from medics, nurses, doctors, and other health care professionals. You deserve to understand your options and choose the path that's right for you. Take charge of your health care and feel empowered to partner with health care providers to achieve the best possible results. Prepare yourself to make the most out of consultations with health care providers Take responsibility for your care or the care of a loved one by partnering with medical professionals Learn how to talk to doctors and ask questions to get the answers that you are looking for Understand your treatment options and stand up for yourself if something doesn't seem right This book is a valuable tool for anyone who uses the healthcare system, especially those who need a high level of care from multiple providers and specialists.